Etiology and clinical manifestations of bacterial liver abscess: A study of 102 cases. Issue 38 (September 2018) - Wang, Wen-Jing; Tao, Zhen; Wu, Hui-Ling
Abstract : Abstract: This study aimed to analyze the clinical manifestations of patients with pyogenic liver abscess and characteristics of pathogenic that caused their infections, in order to provide guidance for the identification of the pathogens that cause liver abscess and selection of antibiotics for treatment of this disease. In the present study, the clinical characteristics, laboratory results, as well as the species and drug resistance of pathogens in patients with bacterial liver abscesses admitted to our hospital from January 2013 to December 2015 were retrospectively analyzed. The patients were treated by ultrasound or CT-guided percutaneous portal vein catheterization and drainage combined with intravenous infusion of antibiotics (the third-generation cephalosporins, the coformulation of carbapenem and dehydropeptidase-I inhibitors, or the coformulation of tazobactam and piperacillin). A total of 178 patients were diagnosed with liver abscess by B ultrasound or CT. The abscesses mostly occurred in elderly male patients and patients with diabetes mellitus. The major clinical and hematological features were fever (163/178, 91.2%), single focal abscess (146/178, 82.0%), elevated white blood cell count, and percentage of neutrophils (136/178, 76.4%). A total of 102 nonrepetitive strains of bacteria were isolated, including Klebsiella pneumoniae (82 strains, 80.3%), Escherichia coli (8 strains), Pseudomonas aeruginosa (2 strains), Acinetobacter baumannii (1 strain), and Gram-positive cocci (9 strains). Susceptibility to antimicrobial drugs was determined by analyzing the minimum inhibitory concentration, and among the 8 cultured E coli strains, 5 strains that could produce extended-spectrum β-lactamase (ESBLs) were among the most commonly seen nosocomial infections. In the present study, bacterial liver abscesses were mostly community-acquired, and K pneumoniae was highly susceptive to the commonly used antibiotics. Five patients had poor outcomes due to infectious shock or the accompanying liver cancer. In other patients, after treatment, the body temperature and the inflammatory indices, such as the total white blood cell count and C-reactive protein, returned to normal levels, and the area of abscess decreased. Most of the bacterial liver abscesses were caused by K pneumoniae, in which only a few strains exhibited resistance to the commonly used antibiotics. The use of ultrasound- or CT-guided percutaneous drainage combined with antibiotics was an appropriate way to treat the liver abscesses of these patients.